MEMBANGUN KARAKTER BANGSA MELALUI PEMBELAJARAN BAHASA INDONESIA - Jazeri, Mohamad; Turrofiah, Ilmia (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia)
Character building is one of the main goals in education. In addition to educating the nation, education is also expected to be the right instrument in character building, both theoretically and practically. A nation that has good character is a nation that implements noble values that grow from the nation itself in various aspects, economic, social, cultural, and also political aspects. There are many media that can be used in building national character, one of which is through learning Indonesian. The purpose of writing this article is to determine the role of the Indonesian language as a medium in instilling the character of the Indonesian nation. The method in this research is descriptive qualitative method with literature study. Data was collected using documentation techniques, namely collecting several research articles on the role of Indonesian language learning in instilling character values. The data analysis found (1) the implementation of Indonesian language learning as an effort to build national character (2) Indonesian language learning is able to foster a national spirit, (3) Indonesian language learning is able to foster a sense of love for the country. This paper discusses the meaning of the word "peace" in the phrase "at peace with COVID". Determination of meaning is based on the context of the phrase "at peace with COVID" or a contextual meaning. Based on the context of the situation, the word peace in the phrase "at peace with COVID" does not mean making an agreement with each other, or stopping to attack each other as in the KBBI. Rather, it means trying to adjust to the new situation so that you can feel peace.